RETRACTED: Study of the impact of anthropogenic activities on the environment: problems and prospects of sustainable nature management - Prodanova Natalia; Naslednikova Margarita; Tarasova Olga (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001